Economic aspects of walnut seedling production on a family farm - Kalanović Bulatović, Branka; Rajić, Zoran; Dimitrijević, Bojan (Economics of Agriculture, 2010)
There are profitable conditions for walnut production in Serbia. However, there is a trade gap of this fruit Recently, a demand for walnut seedlings is in growth. The cause of this is new walnut orchards establishment, but large investments discourage producers. The subject of this paper is the economic analysis of walnut seedling production on a family farm, with the aim at observing the influence of production factor to the economic indexes. Solving problems and tasks set during the research required the use of appropriate methods, including: methods for determining costs, analytical calculations for plant production and methods for determining indicators of economic success of family farms. In addition to these methods was used and the method of comparative analysis. Data on farm production for the years 2006 and 2007 have been used for this paper as well as the results of the former researches as the basis for a detail study of specific problems. On the basis of calculated and analyzed economic indexes, the family farm ran business successfully in both years and managed to have positive financial result, which confirms walnut production profitable, although it has been set on a small area of the family farm.